The combination of chest compression synchronized ventilation and aortic balloon occlusion improve the outcomes of cardiopulmonary resuscitation in swine - Xu, Jiefeng; Khan, Zafar Ullah; Zhang, Minhai; Wang, Jiangang; Zhou, Meiya; Zheng, Zhongjun; Chen, Qijiang; Zhou, Guangju; Zhang, Mao (Frontiers in Medicine, 2022)
Aim: The primary mission of cardiopulmonary resuscitation (CPR) is to provide adequate blood flow and oxygen delivery for restoring spontaneous circulation from cardiac arrest (CA) events. Previously, studies demonstrated that chest compression synchronized ventilation (CCSV) improved systemic oxygen supply during CPR, and aortic balloon occlusion (ABO) augments the efficacy of external CPR by increasing blood perfusion to vital organs. However, both them failed to make a significant improvement in return of spontaneous circulation (ROSC). In this study, we investigated the effects of combined CCSV and ABO on the outcomes of CPR in swine. Methods: Thirty-one male domestic swine were subjected to 8 min of electrically induced and untreated CA followed by 8 min of CPR. CPR was performed by continuous chest compressions and mechanical ventilation. At the beginning of CPR, the animals were randomized to receive intermittent positive pressure ventilation (IPPV, n=10), CCSV (n=7), IPPV+ABO (n=7), or CCSV+ABO (n=7). During CPR, gas exchange and systemic hemodynamics were measured, and ROSC was recorded. After resuscitation, the function and injury biomarkers of vital organs including heart, brain, kidney, and intestine were evaluated. Results: During CPR, PaO2 was significantly higher accompanied by significantly greater regional cerebral oxygen saturation in the CCSV and CCSV+ABO groups than the IPPV group. Coronary perfusion pressure, end-tidal carbon dioxide, and carotid blood flow were significantly increased in the IPPV+ABO and CCSV+ABO groups compared with the IPPV group. ROSC was achieved in five of ten (IPPV), five of seven (CCSV), six of seven (IPPV+ABO), and seven of seven (CCSV+ABO) swine, with the rate of resuscitation success being significantly higher in the CCSV+ABO group than the IPPV group (P=0.044). After resuscitation, significantly improved myocardial and neurological function, and markedly less cardiac, cerebral, renal, and intestinal injuries were observed in the CCSV+ABO group compared with the IPPV group. Conclusions: The combination of CCSV and ABO improved both ventilatory and hemodynamic efficacy during CPR, promoted ROSC, and alleviated post-resuscitation multiple organ injury in swine.